2015
DOI: 10.1007/s13524-015-0370-9
|View full text |Cite
|
Sign up to set email alerts
|

Intrayear Household Income Dynamics and Adolescent School Behavior

Abstract: Economic life for most American households is quite dynamic. Such income instability is an understudied aspect of households' economic contexts that may have distinct consequences for children. We examine the empirical relationship between household income instability, as measured by intrayear income change, and adolescent school behavior outcomes using a nationally representative sample of households with adolescents from the Survey of Income and Program Participation 2004 panel. We find an unfavorable relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 70 publications
(70 reference statements)
5
87
1
Order By: Relevance
“…For example, comprehensive early childhood programmes for children at risk have been shown to have extended benefits over time 34. School plays an important role, because economic deprivation has a strong impact on children's educational achievement,10 35 36 and programmes aiming to improve cognitive and academic outcomes have been shown to be beneficial for children's mental health 34. Thus, future efforts to prevent or mitigate the negative effects of childhood economic deprivation on psychiatric disorder may benefit from integration of strategies that improve school performance among vulnerable youth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, comprehensive early childhood programmes for children at risk have been shown to have extended benefits over time 34. School plays an important role, because economic deprivation has a strong impact on children's educational achievement,10 35 36 and programmes aiming to improve cognitive and academic outcomes have been shown to be beneficial for children's mental health 34. Thus, future efforts to prevent or mitigate the negative effects of childhood economic deprivation on psychiatric disorder may benefit from integration of strategies that improve school performance among vulnerable youth.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only a few studies have examined variation in childhood family income and its association with health and social outcomes 10–12. These studies have found unfavourable relationships between childhood family income instability and children's educational attainment,10 11 development12 and behavioural problems 12. These studies have mostly focused on income fluctuation in general, but have also suggested that income fluctuations may be particularly harmful among low-income families.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches may mask substantial and distinct patterns of poverty dynamics (e.g., duration and stability) over the course of childhood, which may be associated with different childhood experiences, thereby affecting academic achievement. Recently poverty researchers have started to acknowledge that children may experience poverty differently over time due to changes in the depth, stability, and duration of spells of poverty (e.g., [30,31,32,33]). However, no study has yet examined this issue among children of immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…Although many children experience stable economic conditions without poverty throughout their childhood, increasing numbers of children in the United States—including those in so-called middle-class families—have experienced volatile family socioeconomic circumstances in recent decades and an increased likelihood of exposure to poverty [31,34,35]. Studies indicate that more than one-third of all children in the United States experience poverty for at least one year during childhood, and nearly 15% of these experience long spells of poverty lasting at least five years [36].…”
Section: Introductionmentioning
confidence: 99%